(untitled) (LACCEI, 2024)
The lack of an automated system for pipes positioning in Raise Boring mining works (RB) generates time and financial losses for the company due to a greater number of use errors produced by the operators. For this reason, reducing the intervention of users in the RB tunneling and raising process is expected to increase work efficiency. The objective of the project is to design and test, through the implementation of a scale model, a pipe positioning system that operates autonomously from direct and inverse kinematics. The function of the system is to pick up a horizontal tube and place it at the required point in a vertical position or with up to 45° inclination. The robotic arm has 4 degrees of freedom (DOFs). The implementation was done with servo motors and the parts were printed in 3D. The coordinates of the arm positions were obtained through the simulations carried out in Python code, which were compared with the real coordinates of the prototype implementation. After that, an accuracy of 96.29% and an average operation time of 16.21 seconds were obtained in the tests carried out, which demonstrates the effectiveness of the implemented system.